METODE SERVQUAL, KUADRAN IPA, DAN INDEKS PGCV UNTUK MENGANALISIS KUALITAS PELAYANAN RUMAH SAKIT X - Ulfi Nur Alifah; Alan Prahutama; Agus Rusgiyono (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2020)
The quality of service provided by the hospital is very important because it can be used as a reference in determining customer satisfaction. Service quality can be perceived as good and successful if the customer is satisfied with the services and suitable with what customers expect. However, if the services are not suitable with customer expectations, the service quality will be perceived as bad. This study aims to analyze the service quality of X Hospital based on five dimensions of service quality. The data was collected by distributing questionnaires to 64 selected respondents who were patients from Hospital X. Then, the data were calculated the value of the gap between customer expectations and perceptions. Then analyzed using the Importance Performance Analysis method and the Potential Gain Customer Value Index to determine the priority of service quality improvement. Based on the research results, there are only 5 indicators that have a positive gap score, which means that the service quality is suitable with customer expectations. From the Importance Performance Analysis quadrant, the indicators of service quality are spread across four quadrants. From the PGCV index, the indicator of service quality that becomes the first priority for improvement is the ease of access to purchase necessities for patients.